Obesity and inflammatory bowel disease: diagnostic and therapeutic implications. Issue 2 (March 2018) - Swanson, Sophia M.; Harper, Jason; Zisman, Timothy L.
Abstract : Purpose of review: The review summarizes our current understanding of how obesity impacts diagnostic studies and therapies used in inflammatory bowel disease (IBD) as well as the safety and efficacy of medical and surgical weight loss therapies in the obese IBD patient. Recent findings: Many of the diagnostic tools we rely on in the identification and monitoring of IBD can be altered by obesity. Obesity is associated with increased acute phase proteins and fecal calprotectin. It can be more difficult to obtain and interpret cross sectional imaging of obese patients. Recent studies have also shown that common therapies used to treat IBD may be less effective in the obese population and may impact comorbid disease. Our understanding of how best to measure obesity is evolving. In addition to BMI, studies now include measures of visceral adiposity and subcutaneous to visceral adiposity ratios. An emerging area of interest is the safety and efficacy of obesity treatment including bariatric surgery in patients with IBD. A remaining question is how weight loss may alter the course of IBD. Summary: The proportion of obese IBD patients is on the rise. Caring for this population requires a better understanding of how obesity impacts diagnostic testing and therapeutic strategies. The approach to weight loss in this population is complex and future studies are needed to determine the safety of medical or surgical weight loss and its impact on the course of disease.